Impact of COVID-19 pandemic on the daily management of biotechnological therapy in inflammatory bowel disease patients: Reorganisational response in a high-volume Italian inflammatory bowel disease centre. Issue 7 (August 2020) - Scaldaferri, Franco; Pugliese, Daniela; Privitera, Giuseppe; Onali, Sara; Lopetuso, Loris Riccardo; Rizzatti, Gianenrico; Settanni, Carlo Romano; Pizzoferrato, Marco; Schiavoni, Elisa; Turchini, Laura; Amatucci, Valeria; Napolitano, Daniele; et al.
The coronavirus disease 2019 (COVID-19) pandemic is having a major clinical as well as organisational impact on the national health-care system in Italy, particularly in high-volume hospitals which are usually active for many essential clinical needs, including inflammatory bowel disease (IBD). Here, we report major clinical and organisational challenges at a high-volume Italian IBD centre one month after the start of the Italian government's restrictions due to the COVID-19 pandemic. All routine follow-up IBD visits of patients in remission were cancelled or rescheduled for 8–12 weeks' time. However, access to the hospital for therapy or for unstable/relapsing patients was not considered postponable. Everyone attending the centre (e.g. physicians, nurses, administrative personnel and patients) were advised to respect the general recommended rules for hand hygiene and social distancing, to disclose if they had a fever or cough or flu-like symptoms and to wear a surgical mask and gloves. At the entrance of the therapy area, a control station was set up in order to double-check all patients with a clinical interview and conduct thermal scanning. A total of 1451 IBD patients under biotechnological or experimental therapy actively followed in the CEMAD IBD centre were included in the study. About 65% of patients maintained their appointment schedules without major problems, while in 20% of cases planned infusions were delayed because of the patient's decision or practical issues. About 10% of patients receiving subcutaneous therapy were allowed to collect their medicine without a follow-up visit. Finally, 10% of patients living outside the Lazio region requested access to their therapy at a local centre closer to their home. At present, five patients have been found to be positive for SARS-CoV-2 infection but with minimal symptoms, 22 are in 'quarantine' for contact considered to be 'at risk' for the infection. Up to now, none of them has experienced significant symptoms. This study represents the first observational detailed report about short-term impact of the COVID-19 pandemic on patient organisation and management in a high-volume IBD centre.